The great dedicatory inscription of Ramesses II : a Solar-Osirian Tractate at Abydos - Spalinger, Anthony John. (Culture and History of the Ancient Near East, 2009)
This volume covers, for the first time, the interaction of a major historical event with the development of the Egyptian Solar-Osirian theology. Pharaoh Ramesses II visited the sacred area of Abydos soon after his recognition of power at Luxor in Thebes. With him were many high officials, one of whom would be soon appointed to be the high Priest of Amun at Thebes, Nebwenenef. During his visit, the king stressed his personal relationship with his father, Seti I as well as ordering the completion of his temple. By analyzing certain passages within Ramesses' official acccount, the Dedicatory Inscription, with others of Seti, a more nuanced appreciation of the growing theological system of Osirus plus Re, the sun god, comes to the fore. This significance of this is heightened when we remember that the king's account was exhibited in the portico of Seti I's temple. \'Anthony Spalinger's new monograph discusses the Great Dedicatory Inscription and these processes anew by means of perspicuous, accurate, translations of the surviving texts, enlivened by equally stimulating commentaries. These are accompanied likewise by meticulously researched footnotes, which have been marshaled with a diligence for which the author is rightly renowned...All of this is done here with exemplary skill and a fine eye for detail, and our libraries are far the richer for it.\' A.J. Peden